TAV-in-TAV in Failed Homograft - Taha Hatab, MD; Syed Zaid, MD; Priscilla Wessly, MD; Michael J. Reardon, MD; Marvin D. Atkins, MD; Nadeen Faza, MD; Stephen H. Little, MD; Neal S. Kleiman, MD; Sachin S. Goel, MD (JACC: Case Reports, 2023)
A 59-year-old male patient with history of rheumatic heart disease with 3 previous surgical aortic valve replacements with the last one being homograft followed by transcatheter aortic valve implantation in failed homograft presented with severe aortic regurgitation and cardiogenic shock requiring urgent TAV-in-TAV-in homograft. (Level of Difficulty: Advanced.)